Effect of fuel characteristics and operating conditions on NOx emissions during fluidised bed combustion of high moisture biomass with coal. (August 2013) - Akram, M; Garwood, R; Tan, C K
Abstract : Pressed sugar beet pulp with a moisture content of 71% and wood chips with moisture contents of 15 and 55% were cofired with Thoresby coal in a 25 kW thermal capacity bubbling fluidised bed combustor over a wide range of operating conditions. The wood chips were blended with the coal in 50/50 (wt/wt) ratio. The overall moisture content of the blends was 10·3 and 30·3%. The pulp was blended with the coal in 70/30, 60/40 and 50/50 (coal/pulp, wt/wt) ratios. The overall moisture content of the blends was 25·2, 31·8 and 38·3% respectively. Emissions of NOx for the tests are compared with those from coal only firing. The emissions of NOx are found to be lower during cofiring as compared to coal only firing due to lower nitrogen content of biomass fuels. The emissions increased with increase in bed temperature when only coal was fired but decreasde with increase in bed temperature when coal pulp blends were cofired. Moreover, the emissions increase with increase in the amount of excess air. The effect of moisture on the emissions is found to be negligible. The effect of individual fuel characteristics on NOx emissions could not be quantified due to interference of other operating parameters.